Peran Pembiayaan Modal Ventura Syariah Terhadap UMKM pada Masa Covid 19 di Indonesia - Fadillah Ramadhani Siregar; Fitri Adinda Pasaribu; Riza Saharah Piliyang; Nurhayati Harahap (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research is to study and analyze strategies to encourage the MSME economy when the new normal is implemented due to the effects of the Covid19 pandemic. This study uses a descriptive culture methodology, and its findings demonstrate the need for prompt, appropriate and honest action on the part of the government and project leaders to reduce losses due to the pandemic and carry out program evaluations